Optimizing Company Finances Using Business Intelligence in Accounting - Nicholas Renaldo; Suhardjo; Suharti; Suyono; Cecilia (Journal of Applied Business and Technology, 2022)
Business intelligence is the process of collecting, analyzing, and interpreting business data to help companies make informed decisions and improve business performance. In accounting, business intelligence is used to understand financial data and monitor overall business performance. This study aims to link the relationship between business intelligence in accounting. Novelty in this research is the methodology in developing business intelligence research in accounting, as it is relatively new to be applied in accounting and business. An approach that combines quantitative and qualitative analysis is very important in achieving the optimization of company finances. Companies must ensure that they have the right strategies and techniques in place to collect, analyze and utilize this information to achieve their financial goals.